2007
DOI: 10.1124/jpet.107.124784
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological Manipulation of Neuronal Ensemble Activity by Reverse Microdialysis in Freely Moving Rats: A Comparative Study of the Effects of Tetrodotoxin, Lidocaine, and Muscimol

Abstract: To be able to address the question how neurotransmitters or pharmacological agents influence activity of neuronal populations in freely moving animals, the combidrive was developed. The combidrive combines an array of 12 tetrodes to perform ensemble recordings with a moveable and replaceable microdialysis probe to locally administer pharmacological agents. In this study, the effects of cumulative concentrations of tetrodotoxin, lidocaine, and muscimol on neuronal firing activity in the prefrontal cortex were e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
39
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 70 publications
(41 citation statements)
references
References 30 publications
2
39
0
Order By: Relevance
“…Third, the mixed solution of CNQX and TTX used in the present study would have a stronger effect in inactivating the dHP. The effect of TTX was shown to be stronger and last longer than that of lidocaine (van Duuren et al 2007). Therefore, the mixed solution of CNQX and TTX probably inhibited the dHP more greatly and the hippocampal dependency of sPAL may be tested more effectively in this experimental condition.…”
Section: Discussionmentioning
confidence: 94%
“…Third, the mixed solution of CNQX and TTX used in the present study would have a stronger effect in inactivating the dHP. The effect of TTX was shown to be stronger and last longer than that of lidocaine (van Duuren et al 2007). Therefore, the mixed solution of CNQX and TTX probably inhibited the dHP more greatly and the hippocampal dependency of sPAL may be tested more effectively in this experimental condition.…”
Section: Discussionmentioning
confidence: 94%
“…The GABA agonists baclofen plus muscimol (BacÏ©Mus; 0.3 Ï© 0.03 nmol/side, respectively) were chosen to pharmacologically inactivate discrete, often adjacent brain regions, because they produce a rapid and prolonged reduction in neuronal activity without inhibiting fibers of passage (Martin and Ghez, 1999;van Duuren et al, 2007). Immediately before placement in the operant chamber on the test sessions, rats were microinjected with either PBS or BacÏ©Mus into each hemisphere simultaneously in a betweensubjects manner.…”
Section: Methodsmentioning
confidence: 99%
“…Previous studies using similar infusions of 0.3 ÎŒl of baclofen/ muscimol solutions with similar concentrations have observed dissociable effects on behavior when GABA agonists have been infused into adjacent brain regions separated by~1 mm (Floresco et al, 2006;Marquis, Killcross, & Haddon, 2007;Moreira, Masson, Carvalho, & BrandĂŁo, 2007), suggesting that functional spread of these treatments is likely ≀ 1 mm in diameter. Furthermore, neurophysiological studies have shown that administration of muscimol into the brain induces a near complete suppression of neural activity that lasts for over 2 h (van Duuren et al, 2007). Thus, infusion of a combination of both muscimol and baclofen would be expected to induce an inactivation that would persist over the duration of the test sessions used in the present study (25-48 min).…”
Section: Surgery and Microinfusion Protocolmentioning
confidence: 97%